2021
DOI: 10.1155/2021/1244389
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Intelligent Translation Model for English Incorporating Neural Network Migration Learning

Abstract: Under the current artificial intelligence boom, machine translation is a research direction of natural language processing, which has important scientific research value and practical value. In practical applications, the variability of language, the limited capability of representing semantic information, and the scarcity of parallel corpus resources all constrain machine translation towards practicality and popularization. In this paper, we conduct deep mining of source language text data to express complex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…In English teaching in colleges and universities, cultivating students' translation ability and skills is an important teaching goal that plays an important role in improving students' comprehensive English ability [6][7]. At present, English translation still relatively lacks systematic teaching planning and teaching skills training mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In English teaching in colleges and universities, cultivating students' translation ability and skills is an important teaching goal that plays an important role in improving students' comprehensive English ability [6][7]. At present, English translation still relatively lacks systematic teaching planning and teaching skills training mode.…”
Section: Introductionmentioning
confidence: 99%
“…Jiying Liu, Zheng Li and Qiuheng Huang. Applied Mathematics and Nonlinear Sciences, 9(1) (2024)[1][2][3][4][5][6][7][8][9][10][11][12][13][14] …”
mentioning
confidence: 99%
“…As an effective means to address the barriers to cross-language communication, machine translation has been a hot topic of interest for researchers. With the great progress of deep learning research, neural network-based neural machine translation (NMT) has gradually emerged [1][2][3]. At present, many Internet companies provide machine translation services, such as Baidu, Netease, Google, and Sogou.…”
Section: Introductionmentioning
confidence: 99%
“…It can be found that the machine translation has low accuracy and low efficiency. erefore, we should use a more intelligent piece of technology for machine translation [11][12][13][14][15]. In the actual testing process of machine translation products, such as Baidu and Google translation software, the quality of translation results is quite different from that of actual professional manual translation.…”
Section: Introductionmentioning
confidence: 99%